A Sociolinguistics Study : The Analysis of Code Mixing Found in PC Media Magazine - ., I Made Krisna Pranata; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., I Nyoman Pasek Hadi Saputra, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk: (1) menganalisis tipe-tipe campur kode dalam majalah PC Media; dan (2) menjelaskan pengertian campur kode yang ditemukan dalam majalah PC Media. Data yang dikumpulkan melalui studi kepustakaan dan dianalisis dengan metode deskriptif kualitatif. Kemudian hasil analisis akan ditampilkan dalam bentuk diagram dan campur kode yang ditemukan ditampilkan dalam tabel. Penulis mengambil delapan artikel dari dua edisi majalah yang berbeda, dari 42 penemuan yang ada di dalam majalah dirasa cukup untuk mewakili setiap tipe campur kode. Hasil dari analisis mengungkapkan bahwa terdapat 42 tipe campur kode yang masuk ke dalam teori Ho dan Suwito. Hasil prosentase yang didapat adalah: (1) berdasarkan teori Ho; proper nouns (28%), lexical nouns (26%), letters of alphabet (23%), phrases (17%), and short forms (6%); (2) berdasarkan teori Suwito; word insertion (61%), shape baster insertion (21%), and phrase insertion (18%).Kata Kunci : campur kode, sosiolinguistik, majalah PC Media, This study aimed at: (1) analyzing types of code mixing in the PC Media magazine; and (2) describing the meaning of code mixing found in the PC Media magazine. The data was gathered through library research and analyzed by descriptive qualitative method. Then, the result of analysis showed in the form of chart and the code mixing found showed in the form of table.The researcher took eight articles form two different editions of the magazine, from the 42 findings in the magazine it was enough to represent some types of code mixing. The result of the analysis revealed that there were 42 types code mixing included in the theory of Ho and Suwito. The result of percentage obtained: (1) based on Ho’s theory; proper nouns (28%), lexical nouns (26%), letters of alphabet (23%), phrases (17%), and short forms (6%); (2) based on Ho’s theory; word insertion (61%), shape baster insertion (21%), and phrase insertion (18%); (2) based on Suwito’s theory; word insertion (61%), shape baster insertion (21%), and phrase insertion (18%.keyword : code mixing, soclioinguistics, PC Media magazine,